EFFECT OF BRAHMISOHALADI SIROLEPA IN CHILDREN WITH AUTISM SPECTRUM DISORDERS - Anirudhan, *Roshni; Nalinakshan, A (International Journal of Ayurveda and Pharma Research, 2018)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairment in social interaction and communication with restricted interests and repetitive behaviour. The prevalence of ASD has shown an alarming increase in the recent decades ending up to 1 in 90 children. In spite of enormous researches in contemporary medical field, no medicaments have proved to be effective in improving their social behaviour. In Ayurveda, ASD comes under the category of Unmada involving derangement of all the three Doshas (Vishama sannipatha) with predominance of Vata & Pitha. Child friendly and effective procedure based therapy in the form of Sirolepa (application of medicated paste on scalp) is being tried in children with ASD between 3 and 12 years selected from the outpatient cases of Dept. Of Kaumarabhrithya, Government Ayurveda College, Thiruvananthapuram. The present study empirically analysis the efficacy of Sirolepa with Brahmisohaladi with its classical reference in Arogyakalpadruma in the context of Unmada. Children with ASD satisfying the DSM V criteria and having a CARS score above 30 were selected for the study having duration of 28 days. There was an observable improvement in eye contact, attention span and sleep pattern with a marked reduction in hyperactivity. All of the children included in the study were receiving speech as well as psycho therapies and appropriate dietary advice throughout the treatment course. The clinical observation was supported by CARS (Childhood Autism Rating Scale) & ATEC (Autism Treatment Evaluation Checklist) recorded as pre- post evaluation. The changes in CARS and ATEC score were highly significant at 0.05% level (P<0.0005). The study provides the first potential evidence that Brahmisohaladi Sirolepa may be capable of modifying the core social and cognitive defects associated with ASD.